ISSUES OF DIVISION OF POWERS BETWEEN THE RUSSIAN FEDERATION AND ITS SUBJECTS IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS - Roman V. Zelepukin; Anna V. Lipuntsova (Russian Studies in Law and Politics)
Purpose. The purpose of the article is to study the establishment of the level and degree of regulatory support for the delimitation of powers between the Russian Federation and its subjects in the sphere of physical culture and sport, which is due to a number of prerequisites that characterize the relevance of the stated topic. Among them there are changes in the conditions for the development of physical culture and sport, as well as the restructuring of executive bodies in the regions in the context of the reform of public authority. The subject of the research is regulatory legal acts that establish and disclose the powers of authorities and other subjects in the context of the analyzed relations at the federal level and at the level of subjects of the Russian Federation, as well as the activities of authorized public authorities in this sphere.